2021
DOI: 10.1177/1091581821998945
|View full text |Cite
|
Sign up to set email alerts
|

Nonclinical Development of SRK-181: An Anti-Latent TGFβ1 Monoclonal Antibody for the Treatment of Locally Advanced or Metastatic Solid Tumors

Abstract: Checkpoint inhibitors offer a promising immunotherapy strategy for cancer treatment; however, due to primary or acquired resistance, many patients do not achieve lasting clinical responses. Recently, the transforming growth factor-β (TGFβ) signaling pathway has been identified as a potential target to overcome primary resistance, although the nonselective inhibition of multiple TGFβ isoforms has led to dose-limiting cardiotoxicities. SRK-181 is a high-affinity, fully human antibody that selectively binds to la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Antibodies to TGF-β ligand (both to individual and to all TGFβ isoforms) also exist, as do ligand traps (124,(129)(130)(131). Agents targeted at preventing L-TGF-β activation such as integrin inhibitors have already entered clinical trials of inflammatory diseases (125), and antibodies and small molecules blocking L-TGF-β are in preclinical development (132,133). Angiotensin converting enzyme inhibitors and angiotensin-II receptor blockers such as losartan has been evaluated in clinical trials of COVID-19 (NCT04312009 and NCT04312009) given their low cost, worldwide availability as approved drugs for hypertension and heart failure, and their potential modulation of surface expression of the ACE2 receptor where the SARS-CoV-2 spike protein binds for its cellular uptake route.…”
Section: Tgf-β Pathway Inhibitors May Ameliorate Tgf-β Driven Thrombo...mentioning
confidence: 99%
“…Antibodies to TGF-β ligand (both to individual and to all TGFβ isoforms) also exist, as do ligand traps (124,(129)(130)(131). Agents targeted at preventing L-TGF-β activation such as integrin inhibitors have already entered clinical trials of inflammatory diseases (125), and antibodies and small molecules blocking L-TGF-β are in preclinical development (132,133). Angiotensin converting enzyme inhibitors and angiotensin-II receptor blockers such as losartan has been evaluated in clinical trials of COVID-19 (NCT04312009 and NCT04312009) given their low cost, worldwide availability as approved drugs for hypertension and heart failure, and their potential modulation of surface expression of the ACE2 receptor where the SARS-CoV-2 spike protein binds for its cellular uptake route.…”
Section: Tgf-β Pathway Inhibitors May Ameliorate Tgf-β Driven Thrombo...mentioning
confidence: 99%
“…The agent SRK-181 is a high-affinity, fully humanized monoclonal antibody that inhibits latent TGF-β1 activation. Preclinical work has displayed little to no binding to latent TGF-β2 and TGF-β3 isoforms or to active TGF-β growth factors [59]. In mouse tumor models (bladder, melanoma, and breast cancer), SRK-181 (in combination with anti-PD1 therapy) overcame primary anti-PD-1 resistance and showed survival benefit [58].…”
Section: Srk-181mentioning
confidence: 99%
“…A review of 23 mAbs authorized by the European Medicines Agency between 2016 and 2019 6 indicated that short-term toxicity studies were conducted in 2 species for 35% of the mAbs, with the majority of these reducing to 1 species (the NHP in all cases) for the long-term studies. Other publications contain case study examples 7 , 8 or reports for individual mAbs 9 , 10 , 11 that describe the use of 2 species for short and/or long-term studies.…”
Section: Introductionmentioning
confidence: 99%